Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Matematika ditinjau dari Kecerdasan Emosional - Maya Nurfitriyanti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
The purposes of this study are to know: 1) the influence of Jigsaw type cooperative learning model on. 2) the influence of emotional intelligence on mathematics learning outcomes. 3) The interaction between jigsaw type cooperative learning model and emotional intelligence on mathematics learning outcomes. This study is a quantitative research with the experimental method. The statistical test performed is Two Way ANOVA. The samples taken are 60 people with random technique sampling. The results of this study are: 1) there is the influence of learning methods on the learning of mathematics at 5% error level with significant value is 0,023. 2) there is no effect of emotional intelligence on mathematics learning result at 5% error level with significant value is 0,123. 3) there is no interaction between learning method and emotional intelligence to mathematics learning result at 5% error level with significant value 0,286.